Asset-management framework(s) for infrastructure facilities in adverse (post-conflict/disaster-zone/high-alert) conditions - Abuzayan, K.; Whyte, Andrew; Bell, J. (2014)
Public works departments have responsibility to manage and operate (transportation/water/power) infrastructure assets through careful planning and adoption of appropriate (facility) management techniques. Efficient asset-management becomes all the more important for countries subject to post-conflict/post-disaster adversity, not only to reactivate essential services, but also because programs that stimulate civil-engineering industry participation contribute much to recovery rates and can make-up 10% of a (recovering) nation's Gross Domestic Product. A good asset-management model needs to address key activities, communicate respective interconnectivities, and realize best practice. Limited study has been done into asset-management model frameworks that link directly with the change-management strategies required by recovering societies; this presents an obstacle to the prompt implementation of essential asset-management systems in sectors operating in adverse conditions. Asset-management techniques able to take account of the full range of factors in less stable environments require to link contributory variables including: dynamic user-needs analyses, life-cycle analysis, national design specifications, building codes, prefabrication opportunities, procurement routes, and project management tools towards re-build/retro-fitting.This early stage research project presents progress thus far in developing an integrative asset-management framework for infrastructure facilities in adverse/high-alert conditions using a multitude of North African case-study locations. Discussion centers upon developing framework(s) as a basis for workable procedures able to be amended with regard to (changing) design specifications/standards/legislation. Secondary research is presented that addresses the need to integrate economic whole-life evaluation techniques, asset-management tools and scopes in flux, and the extent to which such examination allows future development of flexible change-management for adverse situations towards incorporation into an integrative asset-management framework for infrastructure and civil engineering assets.